THE EFFECT OF E-COMMERCE AND THE USE OF ACCOUNTING INFORMATION SYSTEMS ON THE REVENUE CYCLE OF MICRO, SMALL AND MEDIUM ENTERPRISES - Ami, Aulia Sandina; Syafitri, Lili; Meiriasari, Vhika (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This research aims to analyze and describe the influence exerted by E-commerce and the use of Accounting Information Systems on the Income Cycle of Micro, Small, and Medium Enterprises (MSMEs) in Prabumulih City. The sampling technique used is simple random sampling. The data analysis technique employed in this study was multiple linear regression analysis, which was then processed using the SPSS version 26.0 software application. The data used in this study are primary data collected through a questionnaire, with 100 respondents sourced from MSME actors in Prabumulih City. Several analytical methods were used, including descriptive statistics, classic assumption tests, multiple linear regression tests (such as the coefficient of determination test, R2), t-tests, and F-tests. This research demonstrates that E-commerce has a positive and significant effect on the MSME Revenue Cycle, and the Use of Accounting Information Systems also has a positive and significant effect on the MSME Revenue Cycle. Furthermore, both E-commerce and the Use of Accounting Information Systems have a positive and significant impact on the Income Cycle of MSMEs, both partially and simultaneously.